Manifestações bucais da quimioterapia em mulheres em tratamento de câncer de mama em hospital de referência em Vitória-ES - Musso, Maria Aparecida Amaral (2013)
BACKGROUND: Oral health deserves special attention when dealing with cancer patients because lesions in the oral cavity are the most frequent complications associated with chemotherapy, due to the high sensitivity of oral structures to toxic effects of chemotherapy. OBJECTIVE: This study aimed to evaluate oral manifestations - caries, gingivitis, mucositis, xerostomia and thrush - before and during chemotherapy in women with breast cancer undergoing treatment at St. Rita Hospital, in Vitoria city in the State of ES. METHODOLOGY: This was a longitudinal study conducted in three phases: Moment 1 - before the 1st session of chemotherapy (CT) with a sample of 89 patients; moment 2 - after the 1st session of CT, and now 3 - after the 2nd session CT. Moments 2 and 3 had a final sample of 41 patients. Clinical examinations were carried out - caries, mucositis, xerostomia, gingivitis and thrush - using a semi-structured interview to collect clinical data - color / race, income, education, socioeconomic status, age and comorbidities. Next, descriptive analysis of the data were run by means of frequency tables with numbers and percentages for each of the three stages of the research. The McNemar test was used to determine the direction of the disagreement and the Kappa test was used to identify levels of agreement in three stages. The significance level used in the tests was 5%. The statistical package - Social Science Statistical Package (SPSS) - version 20 was used for analysis. RESULTS: The final sample was composed mostly by women aged above 50 years, with complete basic education, race / white color, socioeconomic status and income of level C up to two minimum wages. Most women needed prosthesis due to the large number of missing teeth. In this study, no statistically significant differences oral manifestations of xerostomia and gingivitis among the three moments; mucositis had only two cases in point 3; sore and showed a statistically significant improvement in the third stage of the research. CONCLUSION: The presence of a dental surgeon is very important in the multidisciplinary team to monitor cancer patients before, during and after neoplastic treatment.